SARANA MAKAN UNTUK MENGATUR POLA MAKAN PENDERITA DIABETUS MELITUS - Bagus Ajidani; Markus Hartono; Wyna Herdiana (Perpustakaan Universitas Surabaya, 2018)
Diabetic is one of the deadly diseases and should be watched our for. This disease in Indonesia is one of the most feared amongst others. Those who have it tend to easily get complications in their internal organs which results in faster death.The purpose of this food medium is to help the diabetics control their eating pattern which could improve the quality of their life by not worsening their health condition. From the research, there will be a set of food mediums with the concept